Validation of the conceptual model of engagement of Instagram social network users’ emotional response level in Iraqi radio - Attwan Mozan Al-Sudani, Inas; Rashidpoor, Ali; Abd-Alrazaq Mostaf Ghrairi, Adel; Sadeghi , Mehrdad (Future of Work and Digital Management Journal, 2026)
The present study was conducted with the aim of validating a conceptual model of engagement and the level of emotional reaction among Instagram users of radio stations in Iraq. The study employed a mixed-methods approach consisting of a qualitative (exploratory) phase and a quantitative (descriptive–survey) phase. In the qualitative phase, data were collected through interviews with 20 experts in the fields of Instagram, digital media, and radio, and the emotional reaction characteristics of users were extracted. In the quantitative phase, the statistical population consisted of 8,000 Instagram users of radio stations in Iraq, and based on Morgan’s table, a sample size of 484 individuals was determined. The validity and reliability of the research instrument were assessed using expert evaluations and Cronbach’s alpha, and data analysis was performed with SPSS 22. The results indicated that the emotional reaction characteristics of users include: ordinary consumers (variance 0.67), passive or silent consumers (0.57), reactive users (0.54), information consumers (0.68), active fans (0.80), aware and participatory supporters and enthusiasts (0.70), content producers and social activists (0.64), and social and political critics and protesters (0.51). Accordingly, the proposed conceptual model was able to significantly explain and validate the different levels of engagement and emotional reaction of Instagram users in relation to radio stations in Iraq.